1996
DOI: 10.1093/cercor/6.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Units Linked to Microvascular Modules in Cerebral Cortex: Response Elements for Imaging the Brain

Abstract: How neuronal activity changes cerebral blood flow is of biological and practical importance. The rodent whisker-barrel system has special merits as a model for studies of changes in local cerebral blood flow (LCBF). Stimulus-evoked changes in neural firing and 'intrinsic signals' recorded through a cranial window were used to define regions of interest for repeated flow measurements. Whisker-activated changes in flow were measured with intravascular markers at the pia. LCBF changes were always prompt and local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
181
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(201 citation statements)
references
References 14 publications
16
181
2
2
Order By: Relevance
“…Our calculations demonstrated that the network behavior is qualitatively independent of d vaso , even though the quantitative results are influenced by its value. In dynamic conditions observed in vivo in rat brains, the magnitude of diameter increases varies from~10% to 45% (Cox et al, 1993;Woolsey et al, 1996;Hillman et al, 2007;Devor et al, 2007;Hutchinson et al, 2006). The maximal value of f vaso (f vaso = 2 corresponding to a 100% vasodilation) used in this study has been overestimated compared to the maximal physiological increase.…”
Section: Blood Flow Control and Passive Responsesmentioning
confidence: 66%
See 3 more Smart Citations
“…Our calculations demonstrated that the network behavior is qualitatively independent of d vaso , even though the quantitative results are influenced by its value. In dynamic conditions observed in vivo in rat brains, the magnitude of diameter increases varies from~10% to 45% (Cox et al, 1993;Woolsey et al, 1996;Hillman et al, 2007;Devor et al, 2007;Hutchinson et al, 2006). The maximal value of f vaso (f vaso = 2 corresponding to a 100% vasodilation) used in this study has been overestimated compared to the maximal physiological increase.…”
Section: Blood Flow Control and Passive Responsesmentioning
confidence: 66%
“…A specific aspect of BOLD contrast where there is continuing controversy on the interpretation of fMRI data is the existence of negative BOLD and its link with neural activity Shmuel et al, 2002;Devor et al, 2007;Northoff et al, 2007;Schridde et al, 2008;Woolsey et al, 1996). In the first paper of this series, Woolsey et al (1996) studied the links between neuronal units and micro-vascular modules in cerebral cortex of the rodent whiskerbarrel system.…”
Section: Hemodynamic Variations Induced By Local Vasodilationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it has been proposed that the change in venous blood volume dominates the total CBV change during altered CBF by neural stimulation and hypercapnia (8,12). However, this assumption is questionable since small arterioles are known to dilate during increased CBF (13)(14)(15).…”
mentioning
confidence: 99%